Programming Conducting Metal‐Organic Frameworks for Catalysis and Energy - Cirujano, Francisco G. (ChemCatChem, 2025)
The dynamics of energy and charge storage/conversion in Metal‐Organic Frameworks (MOFs) are closely linked to their photo‐electro‐catalytic properties, which influence their response toward light, electrons, or ions. Herein, MOFs designed or programmed with geometries and intentionally introduced functionalities are presented, highlighting the advances in defect engineering for increasing reactivity/conductivity and new strategies for enhancing charge transfer dynamics. Several examples of excitation chemistry are reviewed here, including photoexcitation and electrochemical excitation's ability to improve energy/charge transfer, sustainable catalysis, and energy‐related applications of chemical transformations. This review highlights advances in MOF design, including geometry optimization, defect engineering to enhance reactivity and conductivity, and strategies to improve charge transfer dynamics. It also covers excitation chemistry, such as photo‐ and electrochemical excitation, to boost energy/charge transfer and facilitate sustainable catalysis and energy‐related chemical transformations.